Self‐Assembled Structures from Solid Cadmium(II) Acetate in Thiol/Ethanol Solutions: A Novel Type of Organic Chemical Garden. Issue 2 (22nd December 2020) - Bernini, Fabrizio; Castellini, Elena; Sebastianelli, Lorenzo; Bighi, Beatrice; Sainz‐Díaz, Claro Ignacio; Mucci, Adele; Malferrari, Daniele; Ranieri, Antonio; Brigatti, Maria Franca; Borsari, Marco
Abstract: Cadmium(II) acetate in tablet form, immersed in ethanol solutions with a high concentration of heptanethiol (30–80 mM), was able to develop self‐assembled sail‐shaped structures. The solution in which the self‐assembled structure is formed is totally organic (both solute and solvent), thus representing a unique case among organic Chemical Gardens. The constituting material for this new Chemical Garden (CG) is made of a single phase, namely a cadmium heptanethiolate with a microcrystalline structure consisting of a central cluster [Cdn Sn ]. The morphological and structural features were studied using different techniques (SEM‐EDS, elemental analysis, ATR‐FTIR, 113 Cd MAS NMR, XRPD). A crystalline cell for the Cd(II) heptanethiolate cluster was obtained that completely differs from that of the solid phase precipitated by mixing an ethanol solution of Cd(II) acetate with heptanethiol. It follows that the conditions under which the formation of Cd(II) heptanethiolate occurs (slowly from solid, quickly from solution) play a critical role in determining the nature and structure of the precipitating phase. Abstract : Organic Chemical Garden – a challenge : Cadmium acetate and heptanethiol combined give an intriguing Chemical Garden which grows in organic solvent without silicate. The resulting framework is made of densely packed crystals, whose structure is different from that precipitated by mixing ethanol solutions of cadmium acetate and heptanethiol.